Gerakan Masyarakat Hidup Sehat Sadar Pangan Aman (Germas SAPA) dan Waspada Bahan Kimia Obat pada Jamu dan Obat Tradisional di Desa Baturaja Kecamatan Way Lima Kabupaten Pesawaran, Lampung: Healthy Living Community Movement for Safe Food Awareness (Germas SAPA) and Awareness of Chemical Substances in Jamu and Traditional Medicines in Baturaja Village, Way Lima District, Pesawaran Regency, Lampung - Ramdini, Dwi Aulia; Oktoba, Zulpakor; Ulandari, Atri Sri; Parabi, Muhammad Iqbal; Afriyani, Afriyani; Mega, Sri Wulan; Wardhana, Donny Kesuma (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Gerakan Masyarakat Sehat Pangan Aman (Germas SAPA) and Waspada Bahan Kimia Obat in traditional medicines (BKO) are initiatives aimed at enhancing public health degrees in Indonesia. Baturaja Village, located in Way Lima, Pesawaran Regency, is one of the villages that had not yet been exposed to information about these programs. A team of lecturers from the University of Lampung, in collaboration with Balai Besar Pengawan Obat dan Makanan (BBPOM) in Bandar Lampung, conducted a public outreach session for the residents of Baturaja Village. This activity involved an educational session attended by 28 participants, including members of the PKK members and the general public. The session included educational presentations, the distribution of pocketbooks, and questions and answers. Pre- and post-test results on Germas SAPA and BKO awareness showed improved knowledge, with pre-test averages of 8.21 and 8.42, and post-test averages of 9.17 and 9.11. Positive responses were observed from the participants, as demonstrated by their enthusiastic inquiries related to food safety, herbal medicines, and general health. This initiative aims to enhance public understanding of food safety and traditional remedies, with PKK members expected to share this information within the community.